Viktor Gontariv: The Search for National Style and National Form - Naydenko, Viktoriia (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article is devoted to the problem of national style and national form in the work of the modern Ukrainian painter Viktor Gontariv. Today, this problem is acutely relevant due to the threat of losing national uniqueness due to the spread of globalization processes in the world, and the high spiritual values preserved in the centuries-old traditions of national culture are often rejected in favor of the market, fashion, the advance of information technologies, mass culture. This leads to the spread of eclecticism, clichés and simply bad taste. For the first time, the painting of V. Gontariv is considered in the context of the direction of creativity of representatives of the Ukrainian line in Ukrainian fine art of the late 20th – early 21st centuries – A. Antonyuk, F. Humanyuk, I. Marchuk, M. Popov, etc. It is emphasized that the basis of the personal variants of the modern Ukrainian national style of these masters is an appeal to the traditions of Ukrainian folk art, the use of images-symbols and images-metaphors. During the analysis of Gontariv’s paintings, special attention was paid to their close connection with traditional Ukrainian mythology and peasant artistic naivety in the works of folk painters of the 1940s – 1950s in the village Sotnytsky Kozachok, in Slobozhanshchyna, where V. Gontariv was born and spent his childhood, and at the same time his national mentality was formed, which ultimately determined the main line of his work. For the first time, common and distinctive features of the variants of the national style of M. Boichuk’s school and V. Gontariv’s school, though these artists worked in different periods of Ukrainian history, were analyzed. Attention is also drawn to the specifics of the direction of the workshops of V. Gontariv at KSADA and M. Storozhenko at the NAFAA.